Análise socioeconômica de bioprodutos obtidos por pirólise da casca de coco babaçu (Attalea Speciosa Mart ex. Spreng) em comunidades de quebradeiras do Cerrado-Amazônia - Pires, Patricia Silva (Universidade Federal do Tocantins, 2023)
Residues of lignocellulosic biomass from babassu coconut can generate interesting materials for the chemical and food industries. Physical activation processes by cold pressing and slow pyrolysis, as well as physical-chemical activation with zinc chloride (ZnCl2), were developed to produce products such as bio-oil (30%) and biochar (31%), with good income. Charcoal showed good results in terms of adsorption capacity (357 m² g–1 BET surface area) and bio-oil in terms of the possibility of extracting chemical compounds (phenols with 45.81% and aldehydes with 32.76%). In a study applied in another context, and included as a chapter, the main production costs of the process were analyzed, and the results indicate that the proposed process is economically viable and attractive with profits of $422,416.10. Finally, after dialoguing with the coconut breakers and understanding their needs, the viability of economically developing the contacted families was studied through the transfer of technology for the extraction of oil, cake, biochar and bio-oil from the babassu coconut, demonstrating the possibility of generating income based on the profitability achieved in this study.